Multiply (2m + 3)(m2 – 2m + 1).
A. 2m3 – m2 – 8m + 3
B. 2m3 – m2 – 10m + 3
C. 2m3 – 7m2 – 4m + 2
D. 2m3 – m2 – 4m + 3

(2m + 3)(m^2 – 2m + 1) = 2m^3 - 4m^2 + 2m + 3m^2 - 6m + 3 = 2m^3 - m^2 - 4m + 3

s

Question

Asked 10/31/2018 12:40:20 PM

Updated 10/31/2018 7:43:41 PM

1 Answer/Comment

Rating

8

(2m + 3)(m^2 – 2m + 1)

= 2m^3 - 4m^2 + 2m + 3m^2 - 6m + 3

= 2m^3 - m^2 - 4m + 3

= 2m^3 - 4m^2 + 2m + 3m^2 - 6m + 3

= 2m^3 - m^2 - 4m + 3

Added 10/31/2018 7:43:41 PM

This answer has been confirmed as correct and helpful.

Simplify 8 + 2(10 – r).
A. 28 – 2r
B. –2r – 18
C. –2r – 9
D. 7r – 18

Question

Not Answered

Updated 12/29/2018 1:50:05 PM

3 Answers/Comments

8 + 2(10 – r) = 28 - 2r

= 8 + 20 -2r

= 28 -2r

= 8 + 20 -2r

= 28 -2r

Added 10/31/2018 6:35:49 PM

This answer has been added to the Weegy Knowledgebase

8 + 2(10 – r) = 8 + 20 – 2r = 28 – 2r

Added 10/31/2018 6:37:50 PM

This answer has been confirmed as correct and helpful.

Simplify 8 + 2(10 – r)=

"28 – 2r"

Solving

=8 + 2(10 – r)

=8 + 20 - 2r

=28 - 2r

"28 – 2r"

Solving

=8 + 2(10 – r)

=8 + 20 - 2r

=28 - 2r

Added 12/29/2018 1:50:05 PM

2 – (–8) + (–3) =
A. 1
B. 12
C. 14
D. 7

Question

Not Answered

Updated 10/31/2018 1:40:44 PM

1 Answer/Comment

2 – (–8) + (–3) = 2 + 8 - 3 = 10 - 3 = 7

Added 10/31/2018 1:40:44 PM

This answer has been confirmed as correct and helpful.

Solve the following inequality –1 > –2(x – 4) – 5(4x – 7).
A. x > 2
B. x > 8
C. x –23

Question

Not Answered

Updated 10/31/2018 7:41:49 PM

1 Answer/Comment

–1 > –2(x – 4) – 5(4x – 7) ; -1 > -2x + 8 - 20x + 35 ; -1 - 8 - 35 > -2x - 20x ; -44 > -22x ;x < - 44/ - 22 ; x > 2.

Added 10/31/2018 7:41:49 PM

This answer has been confirmed as correct and helpful.

Dave wants to buy a table saw that is worth $291. How much change will he receive if he pays with $300 cash? A. $9.00 B. $582.00 C. $8.00 D. $591.00

Question

Not Answered

Updated 10/31/2018 7:39:42 PM

1 Answer/Comment

32,514,234

questions answered

There are no comments.